Internalisasi Nilai-Nilai Sumbang Duo Baleh sebagai Penguatan Karakter Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah - Dorisno, Dorisno; Frasandy, Rendy; Jannah, Raudhatul; HB, Zulfahmi; Marhamah, Marhamah; Rahmawati, Dwi Nur Ummi; Amalia, Athira Putri (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2024)
Strengthening the character of students in higher education is very important. For this reason, it is necessary to internalize local cultural values. One of the cultures in Indonesia is the Minangkabau culture in West Sumatra. This culture is inseparable from the noble values adopted and developed by the Minangkabau people from the past until now. This study aims to find out more about the internalization of the value of Sumbang Duo Baleh as a strengthening of the character of PGMI students at UIN Imam Bonjol Padang. The research was conducted using a descriptive qualitative research method that describes what it is or provides a clearer picture of strengthening student character with Minangkabau cultural values. The results showed that the internalization of values was implemented through various dimensions including policy, curriculum, learning, student activities, and daily activities. The conclusion is that the internalization of sumbang duo baleh values strengthens student character.